Mall Di Kota Dumai Dengan Pendekatan Arsitektur Postmodern Metafora - Pranata, Shauma Eska; Amanati, Ratna; Firzal, Yohannes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Mall is one of the right choice to be applied in Dumai city because, the increase of population income resulted in higher consumption level, especially with the changing lifestyle of people whotend to spend money to spend and also doing recreation activities. The design approach used to solve design problems is the Tangible Metaphor approach, which is used in planning and designingthe overall expression of the building design. In addition, the application of the concept of building design is also supported by local potentials located in Dumai city, a special feature that reflects the peculiarity that is only found in the city of Dumai. Mall on architecturally is a recreation room and shopping center consisting of shopping complexes where there are buying and selling activities as well as exchange of goods and services as well as tourist attractions and recreation. Mall aredesigned in Dumai city will cause visual and material characteristics that can be felt by visitors who come, not just come to shop but also enjoy the visual of the mall.Keywords: Postmodern Architectural Metaphor, Tangible Metaphor, Mall in Dumai City